Are Manager Policies Associated with Earnings Management Activity? - Yuni Rahmawati; Bayu Triyo Prihatin; Amrie Firmansyah (Universitas Agung Podomoro, 2023)
This study examines the effect of derivative ownership, leverage and tax avoidance on earnings management. This study uses samples from manufacturing sector companies listed on Indonesia Stock Exchange from 2018 to 2021. This research sample consisted of 72 observations based on the purposive sampling technique. Hypothesis testing was carried out using multiple linear regression analysis for panel data. The test results show that derivative ownership has a negative effect on earnings management, while corporate leverage has a positive effect on earnings management. Investors must be concerned about the companies with derivative instruments and corporate leverage because the management of these companies can perform earnings management. In addition, investors and creditors should consider the factors affecting the quality of earnings used to identify and evaluate investment opportunities